PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP WAKTU PELAPORAN KEUANGAN - Wisnu Prima Sakti; Fuad Fuad (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of audit committee characteristics on the financial reporting time. The characteristics of the audit committee used in this study are the independent audit committee, the audit committee's financial expertise, the size of the audit committee and the frequency of audit committee meetings. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2013 to 2017. The method used in collecting data is the documentation method, which is done by collecting the literature related to this study. The total sample used in the analysis was 136 companies. The statistical method used in this study is multiple linear regression analysis. The results of this study indicate that (1) there is a significant influence between the Independent Audit Committee on the Company's Financial Reporting Time, (2) the Audit Committee's Financial Expertise has a positive effect on the Company's Financial Reporting Time, (3) there is no significant influence between the Audit Committee Size and Time of Financial Reporting, and (4) Frequency of Audit Committee Meetings has no significant effect on the Company's Financial Reporting Time.